2021
DOI: 10.21037/atm-21-2924
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical impact of craniopharyngioma classification based on location origin: a multicenter retrospective study

Abstract: Background: An assessment of the clinical impact for craniopharyngiomas (CPs) classification based on origin location has not been reported. The aim of this study was to determine the clinical impact of the site of tumor origin in primary CPs.Methods: Patients from six national institutions who had undergone resection for primary CP were enrolled. Based on the point of origin and surrounding membranous structures, the location of the tumor origin was labelled as Q, S, or T, where Type Q CPs originated below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…This may represent a state of pituitary or hypothalamic disorder and necessitate continuous monitoring as well as individualized electrolyte supplementation. Apart from CP apoplexy, the origin location or the extend of compression on the infundibulum can also affect the incidence rates of these complications ( 27 , 28 ). We further investigated the patients and found that those who presented post-operative electrolyte disturbances, hypothalamic syndrome, or death had more severe compression on the anterior hypothalamus than those who did not (Grade 2 on the image: 11/23 vs. 60/162).…”
Section: Discussionmentioning
confidence: 99%
“…This may represent a state of pituitary or hypothalamic disorder and necessitate continuous monitoring as well as individualized electrolyte supplementation. Apart from CP apoplexy, the origin location or the extend of compression on the infundibulum can also affect the incidence rates of these complications ( 27 , 28 ). We further investigated the patients and found that those who presented post-operative electrolyte disturbances, hypothalamic syndrome, or death had more severe compression on the anterior hypothalamus than those who did not (Grade 2 on the image: 11/23 vs. 60/162).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging also allows for anatomical classification of the tumor as entirely intrasellar, prechiasmatic, retrochiasmatic, or intraventricular [15]. More recently, the QST system has been used to classify craniopharyngiomas as originating from below the diaphragmatic area, or in an infrasellar location (Q); from the precursor cells of Rathke's pouch in the middle or inferior segment of the pituitary stalk (S); and from precursor cells of Rathke's pouch that are located above the pars tuberalis, extending upward into the third ventricle (T), with studies indicating improved and outcomes in type S craniopharyngiomas [9,16]. Prefixed chiasm anatomy, in which the optic chiasm is located over the tuberculum sella, is associated with a narrower surgical corridor between the optic nerves whereas postfixed chiasm anatomy, in which the optic chiasm is located over the dorsum sella, is associated with a wider surgical corridor in this location [17].…”
Section: Surgical Managementmentioning
confidence: 99%
“…According to the 2021 World Health Organization Classification of Tumors of the Central Nervous System, there are two types of CP, adamantinomatous craniopharyngioma (ACP) and papillary craniopharyngioma (PCP), with significantly different etiologies, imaging features, histopathological characteristics, genetic changes, and methylation profiles ( 1 ). ACP is derived from the epithelial cells of the craniopharyngeal canal or residual tissues of Rathke’s pouch, while PCP originates from the residual squamous cells of the original oral fossa ( 2 ). CP accounts for approximately 2–3% of all brain tumors in adults and 6–10% in children.…”
Section: Introductionmentioning
confidence: 99%